PREVENTIVE EFFORTS OF MENTAL HEALTH DISORDERS IN STUDENTS, THROUGH INFORMATION & SUPPORT SERVICES OF COUNSELING SYSTEM - Zain Sarnoto, Ahmad; Rahmawati, Sri Tuti; Ika, Ika; Dian Sari, Windy; Soegiarto, Ita (LP2M IAI Al-Khairat Pamekasan, 2023)
The mental health of students is one of the things that schools need to pay attention to. If mental disorders that arise in students cannot be intervened properly, it will have a negative impact on many aspects. Starting from the emergence of behavior that is not in accordance with school rules, decreased motivation to learn, difficulties in adapting to the environment so that student learning outcomes are not fulfilled at school. Therefore, the purpose of this study is to provide an overview of the various efforts that can be made by schools and Counseling Guidance Teachers to prevent mental health disorders from occurring in students at school. This research was conducted using a type of qualitative research, literature study method. The results of the study show that schools can help maintain students' mental health through programs from guidance and counseling services provided by counseling teachers at schools. These services are in the form of information services and system support. Information services refer to literacy activities regarding mental health in schools while system support takes the form of forming peer counselors and self-care programs. These various efforts can be given to students who are at the junior high school to high school levels.